Sprawozdanie z 54. Tygodnia Eklezjologicznego zorganizowanego przez Koło Naukowe Teologów Katolickiego Uniwersytetu Lubelskiego Jana Pawła II w Lublinie - Pierzchała, Michał (Teologia i Moralność, 2022)
This report is an account on the 54th Ecclesiological Week organised by the Academic Theological Society of the John Paul II Catholic University of Lublin, which took place on 17-19.05.2022.